2016
DOI: 10.1017/s1047951116000196
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic value of plasma N-terminal connective tissue growth factor levels in children with heart failure

Abstract: Plasma N-terminal connective tissue growth factor is a promising diagnostic biomarker for heart failure in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…As regards to relation between CTGF and LV systolic function (EF% and FS%), the current study reported that CTGF was significantly negatively correlated with EF% and FS% measured by echocardiography. This was in agreement with Li G et al [13].…”
Section: Fig 2 Cutoff Sensitivity Specificity Positive Predictivsupporting
confidence: 93%
“…As regards to relation between CTGF and LV systolic function (EF% and FS%), the current study reported that CTGF was significantly negatively correlated with EF% and FS% measured by echocardiography. This was in agreement with Li G et al [13].…”
Section: Fig 2 Cutoff Sensitivity Specificity Positive Predictivsupporting
confidence: 93%
“…There is limited data in pediatric heart failure[45]. Li et al[46] studied CTGF and BNP levels in 61 children including 41 with heart failure. They report that CTGF levels were significantly increased in patients with heart failure and that the levels correlated with the severity of heart failure.…”
Section: Connective Tissue Growth Factor /Ccn2mentioning
confidence: 99%
“…They report that CTGF levels were significantly increased in patients with heart failure and that the levels correlated with the severity of heart failure. Addition of CTGF levels to NT-proBNP levels also improved ability to diagnose heart failure in children[46]. The same group has also shown significant correlation of CTGF levels with pulmonary arterial hypertension associated with CHD in children[47].…”
Section: Connective Tissue Growth Factor /Ccn2mentioning
confidence: 99%
“…In 12–18-month-old children diagnosed with CHD and HF, plasma levels of Growth Differentiation Factor 15 (aka, GDF-15) and beta2-microglobulin (aka, beta2-MG) were positively correlated to the severity of their cardiac function comparing HF vs. healthy controls ( 77 ). As connective tissue growth factors play an important role in several biological such as cell proliferation, angiogenesis and extracellular matrix production, the plasma-N-terminal growth factor was found significantly higher in children with HF compared to healthy volunteers and may be a promising biomarker ( 78 ). Another noteworthy protein, the cardiac-myosin-binding-protein-c (aka cMyBP-C), which is a thick-filament associated protein and a specific cardiomyocyte determinating factor of the structure and integrity of sacromeres, as well as contractile function.…”
Section: Omics Studies For Biomarker Discovery In Chdmentioning
confidence: 99%